A cooperative paradigm for task-space control of multilateral nonlinear teleoperation with bounded inputs and time-varying delays. (October 2019) - Zakerimanesh, Amir; Hashemzadeh, Farzad; Torabi, Ali; Tavakoli, Mahdi
Abstract: In this article, a novel multilateral teleoperation structure is presented for cooperative control of a redundant remote robot in the task-space. In the structure, each local robot is assigned a real number between zero and one, as its dominance factor. The sum of all the assigned factors is equal to one, and a greater dominance factor implies that its corresponding operator will have more power in controlling the remote robot. The time-varying delays in the communication channels, the actuators saturation, and the nonlinear dynamics are incorporated into the controller development. Using Barbalat's lemma and a Lyapunov-Krasovskii functional, the asymptotic stability analysis of the closed-loop dynamics are shown, and the performance claims are delivered. Simulation and experimental results are provided to verify the theoretical findings.